Interface : prize-winning, sustainable modular flooring - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
Interface, Inc., winner of the inaugural Sustainability Survey, is a global corporation which markets modular carpet. This case study examines Interface's commitment to sustainability through its marketing strategy. Readers are asked to evaluate Interface's current position as a leader in sustainable practice and how the corporation can ensure continued success in this area.